Prevalence and molecular characterisation of Schistosoma haematobium among primary school children in Kebbi State, Nigeria - Umar, Shuaibu; Shinkafi, Saadatu Haruna; Hudu, Shuaibu Abdullahi; Neela, Vasantha Kumari; Subbiah, Suresh Kumar; Amin Nordin, Syafinaz; Osman, Malina (Polish Parasitological Society, 2017)
Schistosomiasis is the major source of morbidity in Sub-Saharan Africa and Asia. It is estimated that 207 million people are infected, of which 97% are in Africa. The aim of this study was the determining of prevalence as well as the phylogeny of S. haematobium among school children in Argungu Emirate, Kebbi State Nigeria. A total of 325 urine samples was collected from school children between 7 to 14 years. S. heamatobium eggs was examined under dissecting microscope and DNA was extracted from urine sample and COX1 gene was amplified by nested PCR. The PCR products were purified, sequenced and analysed. This study showed a prevalence of 32.09%, with male pupils having the highest prevalence. S. haematobium infections in children who fetch water in the river have 24 times higher risk of being infected while those who bath in the river have 158 times higher risk of being infected. Our sequences were phylogenetically related to S. haematobium isolate U82266 from Kenya and consistence with the predominant species in Africa. This was the first S. haematobium and S. mansoni co-infection reported in Nigeria. S. haematobium infection is prevalent among school age and significantly associated with water contact.